2014
DOI: 10.1002/jbm.a.35159
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of polyethylene particles induces interferon-γ expression in a natural killer T lymphocyte and dendritic cell coculture systemin vitro: A preliminary study

Abstract: Two major issues in total joint arthroplasty are loosening of implants and osteolysis caused by wear particle-induced inflammation. Wear particles stimulate the release of pro-inflammatory cytokines, chemokines and other inflammatory mediators from macrophages and other cells. Although the biological response of macrophages to wear debris is well established, the role of other cell types such as natural killer T lymphocytes (NKT) and dendritic cells (DCs) is limited. Here we show that ultra-high molecular weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 22 publications
(41 reference statements)
1
8
0
Order By: Relevance
“…Specifically, activated macrophages have been reported to contribute to experimental pain states by releasing factors such as TNFa, IL-1b, IL-8, NGF, nitric oxide, and prostanoids [22,33,37]. In the context of periprosthetic wear debris, joint arthroplasty studies revealed that UHMWPE particles can activate both fibroblasts and macrophages to secrete TNFa and IL-1ß, which can synergistically contribute to the recruitment of more macrophages [19,32]. Accordingly, our previous work showed an increased infiltration of macrophages in TDR tissues containing wear particles [41], and this study confirmed that macrophages (and fibroblasts) produced factors that are known to mediate direct or indirect pain.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, activated macrophages have been reported to contribute to experimental pain states by releasing factors such as TNFa, IL-1b, IL-8, NGF, nitric oxide, and prostanoids [22,33,37]. In the context of periprosthetic wear debris, joint arthroplasty studies revealed that UHMWPE particles can activate both fibroblasts and macrophages to secrete TNFa and IL-1ß, which can synergistically contribute to the recruitment of more macrophages [19,32]. Accordingly, our previous work showed an increased infiltration of macrophages in TDR tissues containing wear particles [41], and this study confirmed that macrophages (and fibroblasts) produced factors that are known to mediate direct or indirect pain.…”
Section: Discussionmentioning
confidence: 99%
“…Despite reported not toxic as metallic particles or studied as polymeric debris [ 12 , 33 , 34 ], ZrO 2 particles should not be neglected, as they are numerous, common and nano-sized with potential to unbalance inflammation towards osteolysis. It has been reported that particle-induced response is prone to drive macrophages towards M1 phenotype and that M1:M2 ratio was higher in synovial membrane-like interface tissue than in OA synovial tissues [ 35 , 36 ]. However, macrophage polarization in joint tissues remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…While wear products do not only induce a local response but also a systemic one [ 16 ], more complex cell culture models have to be established to understand the different interactions of cells. Up to now, there are only a few published studies dealing with co-culture cell models for analysing osteolytic processes in response to wear particles [ 17 , 18 , 19 , 20 , 21 ]. Therefore, we intended to establish the co-culture of human osteoblasts and PBMCs to analyse the impact of cellular interactions in response to metal ion exposure compared to single cell culture experiments.…”
Section: Introductionmentioning
confidence: 99%